DEVELOPMENT OF HIGHER-ORDER THINKING SKILL (HOTS) TEST ON MATHEMATICS IN SECONDARY SCHOOL - Ega Gradini; Cut Khairunnisak; Julia Noviani (UNIVERSITAS MUHAMMADIYAH METRO, 2022)
Assessing students' higher-order thinking skills are still challenging for mathematics teachers in Indonesia. This paper aims to develop a valid, reliable, practical, and effective test to assess students' higher-order thinking skills in mathematics learning. The Plomp’s developmental model, Generic Model for Educational Design, was deployed to develop the test. The method consisted of 4 phases; (1) Problem analysis, (2) Design, (3) Realization, and (4) Evaluation and Implementation. The quality of the developed test was examined by using Plomp’s product quality criteria; (1) Validity, (2) Reliability, (3) Practicality/usability, and (4) Effectiveness. The instruments in this study were validation sheets and practical response questionnaires. The test was validated by expert validation involving two experts on HOTs in mathematics and a trial involving 35 grade 7 secondary school students. The practicality/usability of the test was examined by 25 mathematics teachers from different secondary schools. The effectiveness was measured by trial on three secondary schools. The validity and reliability were measured using Gregory's Expert Agreement Index (EAI). The rubric's practicality was analyzed using practicality product criteria, and the effectivity of the test was analyzed using a two-tailed t-test. The research shows that the validity of the test is 0.88 (high validity), and the reliability is 0.93 (reliable). The practicality of the test is 75.33 (practical). The trial on the lower-index, middle-index, and higher-index schools revealed that the test effectively assessed students' higher-order thinking skills. In conclusion, the HOTs test is valid, reliable, practical, and effective to measure students' higher-order thinking skills in mathematics learning. Menilai keterampilan berpikir tingkat tinggi siswa masih menjadi tantangan bagi guru matematika di Indonesia. Penelitian ini bertujuan untuk mengembangkan tes yang valid, reliabel, praktis, dan efektif untuk menilai kemampuan berpikir tingkat tinggi siswa dalam pembelajaran matematika. Model pengembangan Plomp, the Generic Model for Educational Design, digunakan untuk mengembangkan tes. Metode Plomp terdiri dari 4 fase; (1) Analisis masalah, (2) Perancangan, (3) Realisasi, dan (4) Evaluasi dan Implementasi. Kualitas produk yang dikembangkan diperiksa dengan menggunakan kriteria kualitas produk dari Plomp; (1) Validitas, (2) Reliabilitas, (3) Kepraktisan/kegunaan, dan (4) Efektivitas. Instrumen pada penelitian ini adalah lembar validasi dan angket respon praktikalitas. Produk tes HOTs divalidasi melalui; (1) validasi ahlI yang melibatkan dua validator ahli HOTs matematika dan (2) uji coba yang melibatkan 35 siswa SMP kelas VIII. Praktikalitas tes diuji oleh 25 guru matematika dari SMP yang berbeda. Efektivitas diukur dengan uji coba di tiga SMP/MTs. Validitas dan reliabilitas diukur dengan menggunakan Gregory's Expert Agreement Index (EAI). Kepraktisan rubrik dianalisis menggunakan kriteria produk kepraktisan, dan keefektifan produk dianalisis menggunakan uji-t two-tailed. Hasil penelitian menunjukkan bahwa validitas tes adalah 0,88 (validitas tinggi), dan reliabilitas 0,93 (reliable). Kepraktisan tes mencapai 75,33 (Praktis). Uji coba di sekolah ber-indeks kompetensi rendah, menengah, dan tinggi menemukan bahwa tes HOTs yang dikembangkan efektif untuk mengukur HOTs siswa. Kesimpulannya, tes HOTs yang dikembangkan pada penelitian ini valid, reliabel, praktis, dan efektif dalam mengukur kemampuan berpikir tingkat tinggi siswa dalam pembelajaran matematika.